“Dastur al-katib” as a source on history of state, law and chancellery culture of the Golden Horde (by the example of yarlighs on the appointment of emirs of the ulus) - Abzalov L.F.; Gatin M.S.; Mustakimov I.A.; Pochekaev R.Yu. (Золотоордынское обозрение)
Research objectives: To use historical monuments of Persian origin from the 14th c. as a possible source for the political, legal, and chancellery history in the Jochid Ulus and for specific features of the status of “emir of ulus”, a type of high official in Chinggisid states. Materials and methods of research: The basic materials are yarlighs included into the “Dastur al-katib” of Muhammad b. Hindushah Nakhchivani in its Persian original as well as in German translation by J. von Hammer-Purgstall. The present work also employs other medieval sources on history of the Golden Horde and Iran in the Hulaguid and Jalayir epochs. The methods of research are historical, diplomatic, historical, legal, and comparative historical analysis which amount to an interdisciplinary approach which allows to study historical documents with the highest effectiveness. Scientific novelty: This represents the first Russian translation of the first yarligh on the appointment of the emir of ulus from the “Dastur al-katib” which is studied as a historical source, an example of Mongol chancellery practices, and as a legal monument. Results of the research: The analysis of this document allows one to reconstruct the legal status of the emir of ulus as a high official in Chinggisid states, the requirements for candidates of this position, the rights and obligations of this official, while drawing parallels between similar positions in Iran and the Golden Horde. Comparative diplomatic analysis allows one to clarify similarities in the official paper work in uluses of Hulaguids and Jochids and to confirm the common roots of chancellery traditions in these states that were heirs of the Mongol Empire.